A new genus of Noctuidae (Lepidoptera) from China with the description of two new species - Gyulai, Péter; Saldaitis, Aidas; Vaitonis, Gintas (Zootaxa, 2017)
Descriptions and diagnoses of a new genus Gracilisinensis gen. nov. and two new species G. vaiva sp. nov. and G. moha sp. nov. are provided. The new genus is placed into the subfamily Psaphidinae, tribe Psaphidini. It is most closely related to the genus Diphtherocome Warren.